Cattell’s Personality Factor Questionnaire (CPFQ): Development and Preliminary Study - Primi, Ricardo; Ferreira-Rodrigues, Carla Fernanda; Carvalho, Lucas de Francisco (Paidéia (Ribeirão Preto), 2014)
This study was aimed at: (a) developing an instrument for personality assessment according to Cattell’s model, in which the 16PF is based on; and (b) carrying out an empirical analysis of the internal structure of the instrument. Three hundred and forty seven people, mostly female (67.4%), attending higher education (62.5%) and aged between 16 and 66 (M = 25.69; SD = 8.90) participated in the study. One hundred and twenty items were created and an exploratory factor analysis of the main factors was carried out. Then, a parallel analysis, an exploratory full information factor analysis with categorical variables and an internal consistency analysis were performed. The results suggest that the instrument is composed of 12 factors of reasonable internal consistency rates. The model developed by Cattell helped to understand the structural organization found for the instrument, since there is coherency, especially in relation to more general terms (global factors).